Candida auris: a fungus with identity crisis. Issue 4 (9th July 2020) - Vila, Taissa; Sultan, Ahmed S; Montelongo-Jauregui, Daniel; Jabra-Rizk, Mary Ann
ABSTRACT: Candida auris is a new fungal species that has puzzlingly and simultaneously emerged on five continents. Since its identification in 2009, the scientific community has witnessed an exponential emergence of infection episodes and outbreaks in healthcare facilities world-wide. Candida auris exhibits several concerning features compared to other related Candida species, including persistent colonization of skin and nosocomial surfaces, ability to resist common disinfectants and to spread rapidly among patients. Resistance to multiple drug classes and misidentification by available laboratory identification systems has complicated clinical management, and outcomes of infection have generally been poor with mortality rates approaching 68%. Currently, the origins of C. auris are unclear, and therefore, it is impossible to determine whether environmental and climactic changes were contributing factors in its recent emergence as a pathogen. Nevertheless, a robust response involving rapid diagnostics, prompt interventions and implementation of precautions, are paramount in curtailing the spread of  infections by this fungal species. Importantly, there is a pressing need for the development of new antifungal drugs. In this article, we present a brief overview highlighting some of the important aspects of C. auris epidemiology, pathogenesis and its puzzling global emergence. Abstract : Candida auris is a new multi-drug resistant fungal species that has puzzlingly emerged as a pathogen causing persistent outbreaks in healthcare facilities world-wide with an overall mortality rate approaching 68%.